BASES OF STRESS AND ITS CONSEQUENCES THERAPY AND PROPHYLAXIS IN CHILDREN AND ADOLESCENTS - E. S. Akarachkova; S. V. Vershinina; O. V. Kotova; I. V. Ryabokon' ("Paediatrician" Publishers LLC, 2013)
Physical health of a child is inseparable from his emotional state. At present time it is defined that stress and negative life situations (for example, sudden changes in environment and order of day, beginning and ending of school year, examinations and preparation to them, parents' divorce or dismissal, parting with close friends, interviews etc.) are responsible for increase of distress symptoms in children and adolescents and decrease their ability to self-control. Moreover psychological processes interfere in life activity and can lead to negative consequences in future. The state that emotional and other types of stress can prevent normal psychological and social development in many children is proved in this article. Such disturbances can lead to severe long-term consequences and increase the demand in medical resources, which requires measures aimed to improvement of resistance to stress in childhood and adolescence. During this millennium methods of therapeutic and preventative measures, based on molecular and cellular magnesium-dependent pathogenetic mechanisms of stress formation and consequences of magnesium insufficiency, gain more and more popularity. Recommendations on following certain motional regimen and appropriate for stress condition nutrition do not lose their urgency.